Piloting audience emotion for the television anti-heroine: Gender and immorality. (13th April 2023) - Dean, Levi
The principal aim of this article is to explore how screenwriters can guide audience emotions with respect to the television anti-heroine and encourage their engagement. The model 'piloting audience emotion for the television anti-heroine' will be presented as a screenwriting tool to encourage audience engagement by sequencing specific emotional responses at key points in a pilot episode. This framework is the result of the author's research that explored how audience engagement with a television anti-heroine can be encouraged and comprised of the development of a television show titled Angela . Discoveries made during practice were used to synthesize Aristotle's understanding of pity, fear and catharsis with Murray Smith's structure of sympathy. The model that arose is not an absolute approach, but regardless of its veracity, the conclusions drawn will at the very least promote scholarship concerning the creative development of an anti-heroine screenplay. Before the framework and the specific components comprising it are critically unpacked, the term emotion is first defined within the context of this article.